TINJAUAN KEANDALAN BANGUNAN GEDUNG ADMINISTRASI REKTORAT UNIVERSITAS TEUKU UMAR MEULABOH - Samsunan Samsunan (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2017)
Teuku Umar University in Aceh Barat district of Aceh Province, with potency of earthquake prone according to earthquake zonation map of Minister of Public Works in 2010. The earthquake susceptibility affects the reliability of the building. One of them is the building of Rectorate Administration Building of Teuku Umar University. The building only have component of sloof structure, column, beam and floor plate, has long been neglected and suffered damage to its structure, so it needs to do a reliability investigation in the safety aspect of the building. The reliability investigation is done by field research and then the collecting of primary and secondary data. Concrete strength analysis do by using Concrete Hammer Test tool. Evaluation results show that there is minor damage to some sloof. Conditions of columns have calcification and exfoliation of concrete cover, so that the reinforcement conditions are corroded. While the elements of the beam and floor plate experienced a flexible crack at some point of the beam with a span length of 8 m and on the floor plate. The bending of the beam occurs due to underreinforced or under-dimensional beams that are less able to the load. The result of concrete strength test shows that the average compressive strength of column, beam and floor plate are 174,61 kg/cm2; 205,43 kg/cm2 and 285,17 kg/cm2 with compressive strength of each characteristic 106,85 kg/cm2; 139,69 kg/cm2 and 215,11 kg/cm2. The results of the review and assessment of the field analysis, the building belongs to the category of severe damage, but still feasible to use with some moderate repairs and weight repairs. Structural elements of the beams and columns need to be several repaired and some parts of the sloof and floor plate are moderately repaired. Key word— reliability of building, administrations building, Teuku Umar University